Older veterans associated with reduced risk of cancer: Retrospective nationwide matched cohort study in Taiwan - Pan, Li-Fei; Chang, Renin; Hsu, Chung Y.; Tsui, Kuan-Hao (Frontiers in Medicine, 2023)
Importance It remains unknown whether Taiwanese veterans have a lower risk of subsequent cancer compared with non-veterans. Objective To examine whether veterans are associated with reduced cancer risk. Methods From January 2004 to December 2017, this study included 957 veterans and 957 civilians who were propensity score (PS) matched by years of birth, sex, residence, index year, days in the hospital, frequency of outpatient visits, and relevant comorbidities at baseline. Multivariate Cox proportional hazards regression analysis was applied to compare the risks of cancer, overall and by subgroup, and mortality. All the participants were cancer free at the baseline. Exposures Veterans retrieved from Taiwan National Health Insurance Research Database (NHIRD). Main outcome Cancer extracted from the Registry for Catastrophic Illness Patients Database (RCIPD). Results Overall, 1,914 participants were included, and 957 veterans with a mean (SD) age of 75.9 (6.79) years and 946 men (98.9%). The mean follow-up was about 10.5 (±4.51) years. Cancer was recorded in 6.68% (N = 64) and 12.12% (N = 116) of veterans and non-veterans, respectively. Veterans were associated with decreased risk [adjusted hazard ratio (aHR), 0.57; 95% CI: 0.41–0.78; P < 0.001] of cancer compared with civilians after controlling for age, sex, urbanization, hypertension, diabetes, hyperlipidemia, cardiovascular event, COPD, asthma, chronic liver disease, alcohol-related illness, and Parkinson’s disease. Cancer subgroup analyses verified this finding (HRs <1.0). The decreased incidence rate was predominantly for liver cancer (aHR, 0.18; 95% CI: 0.05–0.72; P < 0.05). Conclusion Taiwanese older veterans are associated with reduced overall cancer risk than individuals without veteran status.